Neurocognitive profile of a young adolescent with DK phocomelia/von Voss phocomelia/von Voss Cherstvoy syndrome. (21st April 2015) - Antonini, Tanya N.; Van Horn Kerne, Valerie; Axelrad, Marni E.; Karaviti, Lefkothea P.; Schwartz, David D.
<x xml:space="preserve">Abstract</x> DK phocomelia/von Voss Cherstvoy syndrome is a rare condition characterized by upper limb and urogenital abnormalities and various brain anomalies. Previously reported cases have noted significant developmental delays, although no formal testing of cognitive abilities has been reported. In this paper we describe results from a comprehensive neuropsychological evaluation of a 12‐year‐old male with DK phocomelia syndrome. Test findings indicated mild impairment in intellectual functioning, with more significant impairment in adaptive skills and academic achievement. The neuropsychological profile converged with neurological findings, showing a distinct pattern of strengths and weaknesses that suggests functional compromise of posterior brain regions with relatively well‐preserved functioning of more anterior regions. Specifically, impairments were evident in perceptual reasoning, visual perception, and visuomotor integration, whereas normal or near normal functioning was evident in memory, receptive language, social cognition, attention, and most aspects of executive functioning. To our knowledge this is the first report to describe the neurocognitive profile of an individual with DK phocomelia syndrome. © 2015 Wiley Periodicals, Inc.